P608 Systematic review: The impact and importance of body composition in Inflammatory Bowel Disease. (21st January 2022) - Ding, N; Tassone, D; Al Bakir, I; Wu, K; Connell, W; Thompson, A; Malietzis, G; Lung, P; Singh, S; Choi, C H; Gabe, S; Jenkins, J; et al.
Abstract: Background: Alterations in body composition are common in Inflammatory Bowel Disease (IBD) and have been associated with differences in patient outcomes. We systematically reviewed the literature to consolidate knowledge on the impact and importance of body composition in IBD. Methods: We conducted a systematic review according to PRISMA guidelines. A systematic search of MEDLINE, EMBASE and conference proceedings was undertaken by combining two key research themes: Inflammatory Bowel Disease and body composition. Studies which examined alterations in body composition in patients with IBD and studies which explored the impact of body composition on IBD therapeutic outcomes and prognosis were included. Results: 55 studies were included in this review. 31 studies focused on the impact of Inflammatory Bowel Disease on body composition with a total of 2, 279 patients and mean age of 38.4 years. Of these, 1, 071 (47%) were male. 1470 (64.5%) patients had CD and 809 (35.5%) had UC. Notably, fat mass and fat-free mass were reduced, and higher rates of sarcopaenia were observed in those with active IBD compared with those in clinical remission and healthy controls. 24 additional studies focused on the impact of derangements in body composition on IBD outcomes. Alterations in body composition were associated with poorer prognoses including higher rates of surgical intervention, post-operative complications, and reduced muscle strength. In addition, higher rates of early treatment failure and primary non-response were seen in patients with myopaenia. Conclusion: Patients with IBD have alterations in body composition parameters in active disease and clinical remission. The impact of body composition on disease outcome and therapy are broad and require further investigation. The augmentation of body composition parameters in the clinical setting has the potential to improve IBD outcomes in the future.